Analysis of Basic Volleyball Skills in Overhead Passing Among Seventh Grade Students at SMPN 3 Bangunrejo - Setiawan, Tri Anjang; Ariesna, Rachmat Dody; Tohir, Ahmad (Jurnal Evaluasi dan Pembelajaran, 2025)
Physical education at the junior high school level requires a comprehensive understanding and mastery of basic sports techniques, one of which is volleyball. The phenomenon that has emerged shows that students' overhand passing skills are uneven and there are still many errors in hand position and ball direction. This problem forms the basis of this study to analyze the level of basic overhand passing skills in seventh grade students at SMPN 3 Bangunrejo. The purpose of this study was to describe students' ability to perform overhead passes in volleyball and to identify factors that affect their accuracy and coordination. This study used a quantitative descriptive approach with observation and performance assessment techniques based on an overhead passing skill test rubric that had been validated by physical education experts. The results showed that most students had moderate passing skills, with an average score of 72.6%. The most mastered aspects were body coordination and response speed, while the weakest aspects were ball direction consistency and power control. Data analysis indicated that playing experience and training frequency influenced skill improvement. The conclusion of the study confirms that systematic training and demonstration-based learning can improve the accuracy and effectiveness of overhand passing techniques. The novelty of this study lies in the application of a quantitative performance-based technique analysis model in assessing students' motor skills, which has rarely been used in the context of junior high school volleyball learning.